Making a newspaper (psychological view) - Amos, Edgar McCall (My University, 1902)
Introduction: In writing on the subject of “Making a Newspaper” from a psychological view, it will not be necessary to dwell upon the mechanical work of the print shop or the kinds of presses and machinery required to run a newspaper. It is apparent that the best available machinery should be used. Our plan is to consider a paper from a printer’s view also the style and arrangements of its contents, especially with its relation to the mind. We go back to the ancient Assyrian Nations, and we see in the undecayed bricks of the tower of Babylon figures and hieroglyphics stamped upon them, and our minds at once revert to the primeval times when the stamping of these tablets was the only mode of printing. The result of this crude method serves us with a history of the days of old. It is here we begin to see the relation of printing to the human mind. The ancients found it necessary to provide some method to aid them in keeping a record of their times, and while these tablets served this purpose to a degree, this mode of printing was absolutely useless as a medium through which literature and learning could be widely propagated. So we see, as time rolled on, the imaginative faculty of the mind was aroused and we reach the period, four centuries ago, when Guttenburg made the simple yet marvelous invention of moveable types. By this art every letter or character of the alphabet was separate and capable of being arranged into words and sentences, thus saving the labor of carving type for each page to be printed. From this time on we find that the art of printing has kept pace with all other improvements and inventions and today it seems to have almost reached perfection.
Citation: Amos, Edgar McCall. Making a newspaper (psychological view). Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Newspaper; Printing; Journalism; Theses